El control interno y su incidencia en el tratamiento de los activos fijos de la unidad educativa Quevedo respecto a la NIC 16, período 2012 - Montesdeoca Núñez, Jenny Pamela (2015)
The internal control is really important for a company structure, because it helps to have an efficient and appropriate control, allowing thus protecting the company resources. Through the evaluating internal control, we can determinate the results of some effectuated proofs with the aim of stablishing the methods, politics and company procedures. The application of the Internal Control in the present research looks for evaluating the Internal Control in the treatment of fixed assets of the Educational Unit Quevedo respect to NIC 16, period 2012. This research began with the use of questionnaires, observations and interviews of the processes in the state and the following results were obtained: confidence level 94.25% high, and a risk level of 5.75% low; concerning the measurement of risks, we have the following; inherent risk 25%, risk of detection 10% so an audit risk of 0.14% was obtained. The evaluation of internal control weaknesses allowed us to detect and provide recommendations to provide proper management of the entity.